Mechanical properties and fire-resistance of composites with marble particles - Abenojar Buendía, Juana; Martínez Casanova, Miguel Ángel; López de Armentia Hernández, Sara; Paz Jiménez, Eva; del Real Romero, Juan Carlos; Velasco López, Francisco Javier (My University, 2021)
The main aim of this work is to manufacture a composite material based on a natural material (marble) with acceptable mechanical properties and fire resistance, for being used in habitat industry as floor or wall in buildings. Marble used as raw material is the waste powder of quarry or plate manufacturing. To achieve this objective, polyester matrix composites with 50 wt.% of marble and 3 wt.% of glass fiber (short fiber or mesh) were prepared. The novelty of this study is the high percentage of ceramic material added to a polymer matrix composite and the fire resistance study. Samples were characterized mechanically through flexural test, Charpy impact test, compression test and wear resistance by pin-on-disk test. Fracture surfaces were analyzed by scanning electron microscope (SEM), and wear tracks were studied by SEM and 3D optical profilometer. Besides, samples were subjected to fire test using a Bunsen burner at 900 °C for 20 min. Sample temperature at the opposite-to-fire test side was measured with an infrared thermometer. Results show that marble improves mechanical properties of polyester and the effect of the glass fiber depends on its morphology (fiber or mesh). Fire resistance is high, and the fire goes out when the flame is turned off. Furthermore, the mesh maintains the integrity of the sample.
Artículos en revistas
Keywords: Instituto de Investigación Tecnológica (IIT)